Interferon-γ Response of Mycobacterium avium subsp. paratuberculosis Infected Goats to Recombinant and Synthetic Mycobacterial Antigens - Köhler, Heike; Liebler-Tenorio, Elisabeth; Hughes, Valerie; Stevenson, Karen; Bakker, Douwe; Willemsen, Peter; Bay, Sylvie; Ganneau, Christelle; Biet, Franck; Vordermeier, H. Martin (Frontiers in Veterinary Science, 2021)
Despite its potential for early diagnosis of Mycobacterium avium subsp. paratuberculosis (MAP) infection, the IFN- release assay is not used routinely, because of low specificity of the established crude antigen preparation Johnin (PPDj). Limited data are available assessing the potential of MAP-derived protein and lipopeptide antigens to replace PPDj in assays for goats, while cattle and sheep have been studied more extensively. Furthermore, MAP infection is claimed to interfere with the diagnosis of bovine tuberculosis when other crude antigen preparations (PPDb, PPDa) are applied. In this study, the diagnostic potential of MAP-derived recombinant protein antigens, synthetic MAP lipopentapeptides and of Mycobacterium bovis-specific peptide cocktails was assessed compared to crude mycobacterial antigen preparations in experimentally infected goats. Goats were inoculated with MAP, or Mycobacterium avium subsp. hominissuis (MAH) as surrogate for environmental mycobacteria, non-exposed animals served as controls. Mycobacterium avium Complex-specific antibody and PPDj-induced IFN- responses were monitored in vivo. Infection status was assessed by pathomorphological findings and bacteriological tissue culture at necropsy one year after inoculation. The IFN- response to 13 recombinant protein antigens of MAP, two synthetic MAP lipopentapeptides and three recombinant peptide cocktails of Mycobacterium bovis was investigated at three defined time points after infection. At necropsy, MAP or MAH infection was confirmed in all inoculated goats, no signs of infection were found in the controls. Antibody formation was first detected 3-6 weeks post infection (wpi) in MAH-inoculated and 11-14 wpi in the MAP-inoculated goats. Maximum PPDj-induced IFN- levels in MAH and MAP exposed animals were recorded 3-6 and 23-26 wpi, respectively. Positive responses continued with large individual variation. Antigens Map 0210c, Map 1693c, Map 2020, Map 3651cT(it) and Map 3651c stimulated increased whole blood IFN- levels in several MAP-inoculated goats compared to MAH inoculated and control animals. These IFN- levels correlated with the intensity of the PPDj-induced responses. The two synthetic lipopentapeptides and the other MAP-derived protein antigens had no discriminatory potential. Stimulation with Mycobacterium bovis peptide cocktails ESAT6-CFP10, Rv3020c and Rv3615c did not elicit IFN- production. Further work is required to investigate if test sensitivity will increase when mixtures of the MAP-derived protein antigens are applied.